A 60‐GHz low‐noise amplifier with +7.258‐dBm third‐order input intercept point using current reuse feedforward distortion cancellation for 5G emerging communication. (6th March 2022) - Veerasamy, Thenmozhi; Manickam, Bhaskar
Abstract: In the ever‐growing 5G technology, the millimetre‐wave (mmWave) frequency spectrum is the inevitable mainstream for high‐speed wireless communication. The wide‐ranging spectrum bandwidth of the mmWave frequency attracts interest in radio frequency (RF) front‐end design which will be very much beneficial for security and cellular‐based applications such as intersatellite communication and automotive vehicle‐to‐vehicle communication. The RF front end requires low‐power and low‐noise receiver architecture for effective satellite communication, and it needs high throughput with maximum data transfer for cellular‐based applications. To address these challenges, this paper presents a novel low‐noise amplifier (LNA) operating from 57.12‐ to 66.25‐GHz frequency. The design is implemented using UMC 65‐nm CMOS process technology, and the post‐layout simulations are carried out using the Cadence Spectre RF tool. At 60 GHz, the LNA exhibits a power gain of 15.46 dB, minimum noise figure (NF) of 1.32 dB while consuming 6.59 mW from a 1.2‐V supply. The LNA employs the current reuse feedforward distortion cancelation technique to improve the third‐order input intercept point (IIP3) to +7.258 dBm. The proposed LNA provides a relatively better figure of merit compared to some of the recently proposed mmWave LNA architectures. Abstract : A 60‐GHz mmWave LNA is proposed for high‐throughput, low‐power, and low‐noise receivers operating in the unlicensed band of 57–66 GHz. The current reuse feedforward distortion cancellation technique for linearity enhancement is employed along with the low‐noise CG input stage which reduces the circuit noise than the ever used 60‐GHz LNA architectures such as CS‐CS and cascode topology.